Memetizing in class: memes, image reading and the challenges of contemporary education (Palíndromo, 2024)
This article aims to investigate the ped-agogical potential of memes in school contexts and debate the contemporary challenges of teaching how to read visual languages. To develop it, a bibliographical research was carried out, based on Cultur-al Studies and Visual Culture Studies, and whose development was divided into two topics. In the first, there was a debate about images as (trans)formers of identities, in-cluding in classrooms. In the second, we contextualize, historically and visually, the creation of memes and thematize the ways in which this artifact of visual culture has been inserted in classrooms, as a teaching resource. In the considerations, we reflect on the expectations and realities of access to technology in contemporary educational spaces, articulating research carried out at different historical moments.
Keywords: cultural studies; visual culture; teacher training; education